Portfolio assessment : Getting started - Fina, Allan A. De.; Ontario; Ontario (New York : Scholastic, 1992)
A concise explanation of what reading, writing portfolios are and how to use them for evaluation and intervention. Includes tips for getting started, management strategies and models from real classrooms.
Includes bibliographical.
Keywords: Portfolio assessment